Wearing colored glasses can influence exercise performance and testosterone concentration? - Londe, A. M.; Marocolo, M.; Coelho Marocolo, I.; Fisher, J.; Barbosa Neto, O.; Campos Souza, M. V.; Ribeiro da Mota, G. (Sports Medicine International Open, 2018)
Perception of red color is associated with higher testosterone concentration and better human performance. Thus, we evaluated the acute effects of wearing colored-lens glasses on the YoYo intermittent endurance exercise test 2 (YoYoIE2) performance indicators and testosterone concentration. Ten soccer players performed three YoYoIE2 (counterbalanced crossover) wearing colorless (control), blue- or red-lensed glasses (2-4 days of rest in between). YoYoIE2 performance did not differ among the trials (p>0.05), but blood testosterone increased post-exercise in red compared to red baseline (red=14%, effect size=0.75). Analysis showed faster heart rate recovery (p<0.05) at 1 min post-test for blue compared to red lenses. Rating of perceived exertion and blood lactate concentration did not differ (p>0.05) among the trials. Wearing red-colored lenses during high-intensity intermittent exercise increased testosterone concentration, but do not influence performance.